The Effectiveness of the Birthing Ball (Gym Ball) on the Progress of Opening the First Stage of Labor in the Working Area of Muka Health Center, Purwakarta District, Purwakarta Regency, Indonesia - Angkut, Cik (HM Publisher, 2023)
The birthing ball allows gravity to help the baby descend into the pelvis, which can speed up the opening of the cervix. Apart from that, the Birthing Ball also provides extra comfort and support to pregnant women, which can reduce pain and anxiety during the birthing process. This study aimed to determine the effectiveness of the birthing ball (gym ball) on the progress of the opening the first stage of labor in the Muka Health Center Working Area, Purwakarta District, Purwakarta Regency, Indonesia. This study is experimental research with a post-test approach with the control group and uses primary data, namely measuring the length of the first stage of labor. A total of 30 research subjects took part in this study. The birth ball showed the potential to increase the speed of duration of the first stage of labor statistically significantly, p<0.05. The duration of the first stage of labor in the intervention group was around 195.83 ± 16.76 minutes, while the duration of labor in the control group was 345.83 ± 26.76 minutes. In conclusion, there is the effectiveness of the birthing ball (gym ball) in the progress of the opening the first stage of labor in the Muka Health Center Working Area, Purwakarta District, Purwakarta Regency, Indonesia.